KINERJA EKONOMI, EFISIENS, DAN EFEKTIVITAS DINAS SOSIAL KABUPATEN MALANG SEBELUM DAN SELAMA PANDEMI - Vanissa Dyah Rahmaprilia; Vega Wafaretta (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2021)
The Social Service of Malang Regency has not applied the concept of value for money in evaluating performance, which consists of economy, efficiency and effectiveness. Several previous studies have analyzed the performance of public sector organizations, but this study fills the gap by comparing performance before and during the pandemic in 2019-2020. The data collected is interview data and financial performance reports. Three programs assessed were office administration service, facilities and infrastructure improvement, and development of the performance and financial reporting system. The result is that the Social Service is included in the category of balanced economic and economic in 2019 and 2020, in which there are no activities whose costs exceed the budget. In addition, overall, the Social Service was more efficient in 2020 as indicated by the lower total realized costs than in 2019, despite the same number of activities. Working from home and decreasing employee mobilization due to pandemic restrictions contribute to efficiency. Regarding effectiveness, the 2020 pandemic conditions did not reduce the achievement of the performance targets. Suggestions for the Social Service are to maintain performance, start performing performance appraisals based on value of money, and be more efficient in using inputs to optimize output.